From Rhetoric to Reality: Warsan Shire's “Home” and the Refugee Crisis (The Informal: South Asian Journal of Human Rights and Social Justice, 2024)
This paper examines Warsan Shire's poem "Home" within the context of the contemporary refugee crisis driven by civil wars in various countries. The paper also discusses how, despite the ideals of open borders and the right to seek safety advocated by globalization, human rights, and the United Nations, refugees frequently encounter difficulties such as humiliation, xenophobic aggression, and discrimination in host nations. Applying Emmanuel Levinas's "politics of hospitality" and Gordon Allport's "contact hypothesis" as theoretical frameworks, this study argues that genuine hospitality, marked by positive interactions and proper integration, is essential for bridging the gap between theoretical principles and the practical treatment of refugees in the domains of human rights discourse and globalization. This study makes a significant contribution by highlighting the challenges faced by asylum seekers in host countries and urging humanity to offer genuine hospitality to mitigate the fears of civil war, terrorism, and other forms of violence.